2020
DOI: 10.1080/15592294.2020.1747742
|View full text |Cite
|
Sign up to set email alerts
|

DNA demethylation is a driver for chick retina regeneration

Abstract: Cellular reprogramming resets the epigenetic landscape to drive shifts in transcriptional programmes and cell identity. The embryonic chick can regenerate a complete neural retina, after retinectomy, via retinal pigment epithelium (RPE) reprogramming in the presence of FGF2. In this study, we systematically analysed the reprogramming competent chick RPE prior to injury, and during different stages of reprogramming. In addition to changes in the expression of genes associated with epigenetic modifications durin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 119 publications
1
19
0
Order By: Relevance
“…In agreement with our previous study, we observed increased expression of GADD45Β in the rRPE, and it is possible that GADD45B regulates DNA methylation to facilitate the epigenetic reprogramming of RPE (Supplementary File S2) [23]. As noted prior, and in agreement with previous studies, the neural retinal progenitor marker VSX2 was identified as one of the top up-regulated DEGs in rRPE (Figure 3b) [18].…”
Section: Transcriptome Changes In the Early Rrpe Reflect Mapk Signalisupporting
confidence: 92%
See 3 more Smart Citations
“…In agreement with our previous study, we observed increased expression of GADD45Β in the rRPE, and it is possible that GADD45B regulates DNA methylation to facilitate the epigenetic reprogramming of RPE (Supplementary File S2) [23]. As noted prior, and in agreement with previous studies, the neural retinal progenitor marker VSX2 was identified as one of the top up-regulated DEGs in rRPE (Figure 3b) [18].…”
Section: Transcriptome Changes In the Early Rrpe Reflect Mapk Signalisupporting
confidence: 92%
“…The limited plasticity observed in mammals stands in contrast to organisms such as urodele amphibians and the chick embryo (Gallus gallus), which have the ability to fully regenerate their retina after damage [4,[12][13][14]. The embryonic chick can regenerate its retina between embryonic day (E) 4-4.5 (Hamburger & Hamilton stages [23][24][25] by reprogramming RPE cells into retinal progenitors that are capable of generating all major retinal cell types [4,12,[15][16][17]. RPE reprogramming in the chick has been characterized at the molecular level in 3 distinct phases [18].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our current hypothesis is therefore that Decitabine delays regeneration through its hypomethylating effect and therefore that DNA methylation may be required for proper regeneration in P. dumerilii . This hypothesis is at odds with what has been described in vertebrates in which, in contrast, demethylation has been suggested to be a driver of regeneration, in the axolotl limb [37], zebrafish fin [36] and the chick retina [80]. Additional experiments will be required to further test the requirement of DNA methylation in P. dumerilii regeneration and identify the involved mechanisms.…”
Section: Discussionmentioning
confidence: 95%